Modern practical healthcare issues in biomedical instrumentation - Ozsahin, Dilber Uzun; Ozsahin, Ilker (Academic Press, an imprint of Elsevier, 2022)
Modern Practical Healthcare Issues in Biomedical Instrumentation describes the designs, applications and principles of several medical devices used in hospitals and at home. The book presents practical devices that can potentially be used for healthcare purposes. Sections cover the use of biosensors to monitor the physiological properties of the human body, focusing on devices used to evaluate, measure and manipulate the biological system, and highlighting practical devices that can potentially be used for healthcare purposes. It is an excellent resource for undergraduate, graduate and post-graduate students of biomedical engineering.- Focuses on devices used to evaluate, measure and manipulate the biological system- Describes the designs, applications and principles of several medical devices used in hospitals and at home- Discusses various application and how their usage will help to aid health care delivery